2019
DOI: 10.1111/jpn.13072
|View full text |Cite
|
Sign up to set email alerts
|

Leucine‐induced promotion of post‐absorptive EAA utilization and hepatic gluconeogenesis contributes to protein synthesis in skeletal muscle of dairy calves

Abstract: The high rate of protein synthesis in skeletal muscle of dairy calves can benefit their first lactation even lifetime milk yield. Since the rate of protein synthesis is relatively low in the post‐absorptive state, the aim of this research was to determine whether leucine supplementation could increase the post‐absorptive essential amino acid (EAA) utilization and protein synthesis in the skeletal muscle. Ten male neonatal dairy calves (38 ± 3 kg) were randomly assigned to either the control (CON, no leucine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Leucine mainly serves as a substrate for protein synthesis and is widely used in the estimation of protein synthesis in heifers ( 36 ). Furthermore, a recent study demonstrated that leucine could also act as a signal to increase the rate of protein synthesis in the skeletal muscle of calves ( 37 ). In this study, concentrate supplementation increased the concentrations of glutamine and leucine, indicating that supply feeding can influence protein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Leucine mainly serves as a substrate for protein synthesis and is widely used in the estimation of protein synthesis in heifers ( 36 ). Furthermore, a recent study demonstrated that leucine could also act as a signal to increase the rate of protein synthesis in the skeletal muscle of calves ( 37 ). In this study, concentrate supplementation increased the concentrations of glutamine and leucine, indicating that supply feeding can influence protein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 38 ] found that leucine stimulated mTOR signal passage and affected skeletal muscle protein synthesis. Similarly, Zheng et al [ 39 ] also found that leucine could activate the mTOR signaling pathway, thereby enhancing the phosphorylation expression of its downstream signaling molecules S6K1 and Eif4E and finally promoting protein synthesis in dairy cow skeletal muscle. S6K1 mainly accelerates protein synthesis by enhancing translation initiation factors [ 40 ], while Eif4E promotes protein synthesis by stimulating the translation of a subset of mRNAs with 5`-terminal pyrimidine motifs [ 41 ].…”
Section: Discussionmentioning
confidence: 95%
“…Leucine can strongly stimulate skeletal muscle anabolism and overcome the anabolism resistance of aging [ 134 ]. In addition, leucine can promote the protein synthesis of skeletal muscle and the transformation of muscle fiber types from fast muscle to slow muscle [ 136 ].…”
Section: Faas As Potential Treatments For Autophagy-related Diseasesmentioning
confidence: 99%